Effects of N, P, K and S application on yield and quality of white jute (Corchorus capsularis L.) var. BJC-2197 - Khanom, Sayma; Hosssain, Sonia; Hossain, Shahid Akhtar (Dhaka University Journal of Biological Sciences, 2012)
A field experiment was conducted at Bangladesh Jute Research Institute (BJRI) to observe the response of N, P, K and S on a pre?released white jute (Corchorus capsularis) var. BJC?2197. The experiment was carried out by applying N, P, K, S fertilizers in ten combinations including control. From the experiment it was observed that all the treatments had significant positive effect over control on growth, yield and quality parameters. The highest fiber yield (3.21 t/ha) and stick yield (6.58 t/ha) were recorded with N90P5K30S10 kg/ha treatment. However, the best quality fiber was found with combination of N90P15K30S10 kg/ha treatment. From the economic analysis point of view, it was found that combination of N90P5K30S10 kg/ha was higher (2.30) than N90P15K30S10 kg/ha (2.04). So the former can be considered as the best combination for var. BJC?2197 in terms of BCR, yield and quality. Dhaka Univ. J. Biol. Sci. 21(2): 109?116, 2012 (July) DOI: http://dx.doi.org/10.3329/dujbs.v21i2.11508